Assessment of Midterm Functional Outcomes Following Talar Extrusion Injuries. Issue 1 (January 2022) - Jha, Shilpa; Atkinson, Kate; McFegan, Matthew R.; Patel, Amit; Vris, Alexandros; Heidari, Nima; Parker, Lee; Jeyaseelan, Luckshmana A.; Romans, Francesc Malagelada
Category: Ankle; Hindfoot; Trauma Introduction/Purpose: Open talar dislocations with complete or partial extrusion of the talus are rare, high energy injuries associated with major complications including infection, avascular necrosis and post-traumatic arthritis. These are debilitating injuries with significant long-term effects including avascular necrosis and post traumatic arthritis. Functional outcome data in the literature is limited and predominantly consists of case reports and few single centre case series. Historically these injuries have been treated with talectomy and tibiocalcaneal arthrodesis, however there has been a subsequent trend towards debridement and reimplantation with preservation of the extruded talus. Our aim was to evaluate mid-term functional outcomes, assess complication profile and need for secondary surgery in a single-centre series of cases treated with reimplantation. Methods: All talar extrusion injuries presenting between January 2015 and January 2018 were identified from the trauma database search at our major trauma centre. Inclusion criteria was defined as open talar dislocations associated with either complete or partial extrusion of the talus. Case-note review was performed collecting baseline demographic data including age, gender, injury mechanism, associated injuries, Gustilo-Anderson grade, smoking and diabetes status, and method and timing of surgical management. Twelve patients were identified with a mean follow-up of 3 years (minimum 26 months). Primary outcome measure was functional outcome assessed using the Manchester-Oxford Foot Questionnaire (MOxFQ). Results for each of the three domains were converted to a 0-100 scale for comparison. Secondary outcomes included complication rate and all cause re- operation rates Results: Mean age was 37.8 years (17-74 years). Five patients (42%) had total talar extrusion without fracture and 7/12 (58%) sustained fracture-dislocation with partial talar extrusion. All were Gustilo-Anderson grade III. All underwent successful reimplantation with 8/12 (67%) treated with single stage surgery, and 4/12 (33%) in two stages. The mean MOxFQ scores for total talar extrusions versus partial talar extrusions with fracture were 79 (range 9-18) vs 41 (range 0-86) for walking domain, 65 (range 45-80) vs 42 (range 0-90) for pain domain, and 63 (range 38-75) vs 48 (range 19-51) for social domain. One patient (8%) developed avascular necrosis, 3/12 (25%) developed infection and 1/12 (8%) patient eventually required below knee amputation. One (8%) patient underwent secondary surgery fusion for post-traumatic arthritis. Conclusion: Our series demonstrates the serious ramifications of sustaining talar extrusions. Patients who sustain these injuries should expect persistent functional deficit and pain at mid-term follow-up. Functional outcomes are relatively poor. The data demonstrates a trend towards better functional outcomes in patients who have partial extrusion of the talar dome with associated fractures, compared to ligamentous total talar extrusion injuries. The incidence of avascular necrosis, deep infection and secondary surgery in our cohort supports reimplantation as an effective treatment strategy.